INFORMATION WAR AGAINST UKRAINE AND LEGAL MEANS TO COUNTER ILLEGAL ACTIONS - Sopilko, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
As you know, Ukraine has long been drawn into a hybrid war, an integral element of which is the information war. In the context of the latter, cybernetic warfare also stands out. In general, attempts to influence the consciousness of individuals and even entire social groups with the help of information have been known since the emergence of the human race, as evidenced by founded traditions and stereotypes. At this stage of human development, when the use of information networks has become an integral element of daily interaction, it is information weapons that have become the main tool and driving force among the world’s power actors. For more than eight years, the Russian Federation has waged hybrid war against Ukraine. In February 2022, Russia began ruthlessly killing Ukrainian civilians, bombing non-military facilities, and in other ways violating the norms and foundations of international law in general and international humanitarian law in particular. At the same time, with no less fury, the aggressor country is trying to exert an informational influence both on the citizens of Ukraine by throwing in fakes and propaganda, and on its people, placing them in an information vacuum. There are attempts by the adversary to gain control over the means of transmitting information, especially concerning the World Wide Web. The purpose of such actions is to force people to think in the way the enemy wants, to impose his goals and principles on the victims. Therefore, it is important to know what an information war is, no less valuable for every Ukrainian will be an understanding of how to counteract the aggressive actions of the enemy in the information space. A detailed acquaintance with the legal methods of countering illegal activity during the information war will help Ukrainians protect their information rights and interests. This is what will be discussed in this scientific study. Purpose of the paper: to study the features and essence of the information war and give recommendations on the legal regulation of relevant issues in Ukraine. Research methods: this scientific article was written by the author using generally recognized methods of scientific knowledge, namely, analytical, formal, comparative-legal, system-structural, and others. Results: the concept, essence, characteristics of information warfare and related categories are analyzed, the problems of ensuring counteraction to malicious acts in this area are indicated, recommendations are provided for overcoming such problems by improving the current legislation, including through the experience of other countries and harmonizing the current regulatory framework with EU standards. Discussion: the dialogue in the scientific study is about the peculiarities of the legal regulation of the threats and risks faced by Ukraine during the hybrid and forthright information war waged against it.